Public-empowering justice : Arguments from effectiveness, legitimacy and democracy, and the South African case - Diana R. Gordon (Punishment Society 2007; 9; 49, 2007)
In mature democracies citizens are being gradually empowered to make important decisions about how to handle crime and disorder and to assume an active role in making their communities safer. Do the justifications for this partial shift away from the commitment to adversarial, state-centered criminal justice apply to democratizing countries? Viewed individually, the arguments for public-empowering justice in Transitional states are all quite partial. But they can be creatively combined within a framework that has relevance for a number of countries, especially if the argument from democracy incorporates a deliberative perspective. Significant institutional barriers remain, however, as illustrated by the post-apartheid South African state's retreat from its initial interest in community policing, lay assessors in criminal trials, and community courts.